Biological performance and sludge filterability of anaerobic membrane bioreactors under nitrogen limited and supplied conditions. (15th June 2018) - Dereli, Recep Kaan; Wang, Xiaofei; van der Zee, Frank P.; van Lier, Jules B.
Abstract: The impact of nitrogen on biological performance and sludge filterability of anaerobic membrane bioreactors was investigated in two lab-scale cross-flow anaerobic membrane bioreactors that were fed with cheese whey at two different COD:TKN ratios (50 and 190). Nitrogen deprivation adversely affected the biological treatment performance and reactor stability, as indicated by volatile fatty acids accumulation. On the other hand, nitrogen (urea) supplementation resulted in a reduced sludge median particle size and decreased sludge filterability. Standard filterability parameters such as capillary suction time and specific resistance to filtration tended to rapidly increase in the nitrogen supplemented reactor. The critical fluxes in the nitrogen limited and supplemented reactors were 20 and 9 L m −2 h −1, respectively. The rapid deterioration of sludge filterability under nitrogen supplemented conditions was attributed to abundant growth of dispersed biomass. Thus, the COD:TKN ratio of wastewater affected both bioconversion and filterability performance in the anaerobic membrane bioreactors. Highlights: Two AnMBRs were operated with substrate COD:TKN ratios of 50 and 190. High COD:TKN ratio adversely affected the bioreactor stability. Filterability indicators, e.g., CST and SRF, were better at higher COD:TKN ratio. Filterability deteriorated due to dispersed biomass growth in urea added reactor.